Prevention of nosocomial COVID-19 infections in otorhinolaryngology-head and neck surgery - Jie Ren (KeAi Communications Co., Ltd., 2020)
Coronavirus disease 2019 (COVID-19) has rapidly evolved into a pandemic, causing a global public health crisis. Many frontline healthcare workers providing ear, nose and throat services have been reported to contract COVID-19 at work. Early during the COVID-19 outbreak, several medical professionals in Otolaryngology-Head and Neck Surgery were infected in Wuhan, China. A series of measures were then taken immediately, which successfully halted the spread of the disease. Here we would like to share the lessons we have learned, and our experience to protect our health care workers during the COVID-19 pandemic.